Experiments on Fishing Net Preservation - Miyamoto, H; Shariff, A T (Indian Journal of Fisheries, 2016)
IT is common knowledge that fishing nets deteriorate either while in use or in storage. The weakening of fibres of the fishing nets is caused by physical wear and tear, bacterial infection, action of organic matter like the fish slime, dead fish, etc., and temperature (Whiteleather, R. T. and Brown, H. H., 1945). All methods of preservation of fishing nets are meant to slow down the processes of deterioration. The Indian fishermen since ages are known to keep their fishing gears in good condition as long as possible, by treating them with some form of vegetable matter like the fruits, the nuts, the leaves and the barks of several trees. Though considerable progress has been made in other countries in the manufacture of net preservatives on a commercial scale and in the study of their advantageous application to diflferent types of fishing gears, no systematic work has been done in India and other tropical countries, even on a study of the vast resources of vegetable products in different forms available in large quantities and used in diflferent parts of the country, the methods of preservation adopted in each case, how far the nets become strengthened by the application of these preservatives, the preserving qualities of each preservative, etc. Attempts have been made, therefore, in these series of experiments for a study of the above details and to observe how far they Â compare with the preservatives used in other parts of the world.